Hepatocellular carcinoma with subcutaneous metastasis - Tezcan, Yilmaz (Radiology and oncology (Ljubljana), 2011)
Background. The majority of subcutaneous metastases from hepatocellular carcinoma (HCC) originate from needle tracks or surgical wound contamination. Non-iatrogenic subcutaneous metastasis from hepatocellular carcinoma was rarely reported. Case report. A 70-year-old man presented with a mass in his left occipital region of the scalp. The surgical complete resection was performed. The histopathology report of the scalp mass showed a characteristicmetastatic HCC. Computed tomography (CT) of the abdomen showed no primary or metastatic lesion in the abdomen; thatćs why the adjuvant treatment was not given after the surgery. Five months later, magnetic resonance imaging (MRI) of the brain revealed a 6 x 5.5 cm mass at the left posterior parietal region of the scalp. Second surgery was performed and histopathology of the specimen excised was again metastatic HCC. The external beam radiation therapy (XRT) was administered after the surgery. A follow-up MRI of the brain showed no recurrent disease after 9 months from XRT. Conclusions. HCCs should be considered in the differential diagnosis of carcinomas metastatic to the skin, even in the absence of liver symptoms.
Keywords: Aged; Brain; Carcinoma, Hepatocellular; Jetra, novotvorbe; Karcinom hepatocelični; Kožne novotvorbe; Lasišče; Liver Neoplasms; Magnetic Resonance Imaging; Magnetna resonanca; Možgani; Radiotherapy; Scalp; Secondary; Skin Neoplasms; Starostniki; Surgery